Iklim Sekolah Terhadap Motivasi Kerja Guru - Sri Mures Walef; Syahril Syahril; Rifma Rifma (Journal Of Administration and Educational Management (ALIGNMENT), 2023)
This study aims to determine teacher work motivation, school climate and the contribution of school climate to the performance of Payakumbuh Vocational High School teachers. This type of research uses a quantitative description method using a correlation research design. The population in this study amounted to 164 people with a sample of 52 teachers using a stratified proportional random sampling technique. The research instrument used a questionnaire with a Likert scale model which was validated first. The results showed that the school climate in Payakumbuh City Vocational High School was classified as sufficient, teacher performance motivation was in the good category and there was a significant contribution from school climate to teacher work motivation in Payakumbuh City Vocational School. In conclusion, the school climate contributes to the work motivation of Payakumbuh Vocational High School teachers. Keywords: Motivation, School Climate, Teacher Performance